2016
DOI: 10.1128/aac.00956-16
|View full text |Cite
|
Sign up to set email alerts
|

Griffithsin-Modified Electrospun Fibers as a Delivery Scaffold To Prevent HIV Infection

Abstract: Despite current prophylactic strategies, sexually transmitted infections (STIs) remain significant contributors to global health challenges, spurring the development of new multipurpose delivery technologies to protect individuals from and treat virus infections. However, there are few methods currently available to prevent and no method to date that cures human immunodeficiency virus (HIV) infection or combinations of STIs. While current oral and topical preexposure prophylaxes have protected against HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 85 publications
0
36
0
Order By: Relevance
“…For blank EFs, 15–20% PLGA w/w and 12–20% PLCL w/w were dissolved in either 3 mL TFE or HFIP solvent overnight while shaking at 37°C. The following day, 2 mL of PLGA or PLCL solution was aspirated into, and electrospun from, a 3 mL plastic syringe as previously described [26, 35]. All formulations were electrospun with a flow rate of 2.0 mL/hr and an applied voltage of 20 kV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For blank EFs, 15–20% PLGA w/w and 12–20% PLCL w/w were dissolved in either 3 mL TFE or HFIP solvent overnight while shaking at 37°C. The following day, 2 mL of PLGA or PLCL solution was aspirated into, and electrospun from, a 3 mL plastic syringe as previously described [26, 35]. All formulations were electrospun with a flow rate of 2.0 mL/hr and an applied voltage of 20 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the advantages of EFs include the ability to highly incorporate a diversity of active agents including drugs and biologics [25, 26], to tailor sustained-release by selecting different polymeric materials, and to maintain agent stability during the course of delivery [27, 28]. Biodegradable polymers, such as poly(lactic-co-glycolic acid (PLGA) and poly(caprolactone) (PCL), are approved by the U.S. Food and Drug Administration (FDA) for therapeutic use, indicating their proven biocompatibility and potential for translation [29].…”
Section: Introductionmentioning
confidence: 99%
“…This novel platform released more than 80% of its payload within 1 h in the presence of seminal hyaluronidase. Grooms et al loaded GRFT on the surface of adhesive fibers to impede HIV-1 entry into the epithelium via physical and chemical barriers [120]. This study showed the utility of fibers for biomolecule incorporation and the ability to introduce physicochemical modifications.…”
Section: On-demand Vaginal Rectal and Dual Compartment Dosage Formsmentioning
confidence: 93%
“…MVC has been formulated into both coaxial electrospun fibers with an ethylcellulose core and polyvinylpyrrolidone (PVP) shell [26], as well as amorphous solid dispersions in PVP and PEO [51]. Grooms et al investigated the effect of incorporating griffithsin (GRFT), a protein that has been shown to have potent activity against both HIV-1 and HSV-2, by grafting the biologic onto the surface of electrospun fibers, as opposed to encapsulating GRFT within the fiber [52]. As opposed to using drug-eluting fibers to prevent infection, Huang et al coated polystyrene fibers with poly(allylamine hydrochloride) (PAH) or dextran sulfate sodium (DSS) and observed inactivation of HIV-1 and a reduction of CD4+ TZMbl cells in the presence of replication competent HIV-1[53].…”
Section: Electrospun Fibers For Female Reproductive Challenges: Cumentioning
confidence: 99%